Association between 24-hour movement behaviors and perceived stress in Chinese university students: a compositional data analysis - Dong, Defeng; Qu, Yanhe; Zhang, Dianbo; Dong, Chen (Frontiers in Psychology, 2025)
ObjectiveThis study used objectively measured data and compositional data analysis to examine the relationship between 24-hour movement behaviors and perceived stress in Chinese university students.MethodsCross-sectional data were collected from 208 Chinese university students (mean age = 20.23 years, 52.9% female). Accelerometers were used to measure 24-hour movement behaviors, including moderate-to-vigorous physical activity (MVPA), light physical activity (LPA), sedentary behavior (SB), and sleep. The Perceived Stress Scale (PSS-14) assessed perceived stress. Compositional data methods were applied to analyze the relationship between the proportion of time spent in 24-hour activities and perceived stress.ResultsCompositional regression analysis indicated that time spent in MVPA (β = −2.55, p < 0.05) and LPA (β = −3.39, p < 0.05) was inversely associated with perceived stress, while SB (β = 7.95, p < 0.05) was positively associated. Sleep time (β = −2.29, p > 0.05) was not significantly related to perceived stress. Isotemporal substitution models further showed that replacing SB with MVPA, LPA, or sleep was associated with significant reductions in perceived stress scores, whereas reallocating time from MVPA, LPA, or sleep to SB was linked to significant stress increases.ConclusionThe proportion of time spent in MVPA and LPA was negatively associated with perceived stress among university students. Replacing sedentary behavior with MVPA or LPA was associated with lower perceived stress. However, these findings should be interpreted with caution due to the study’s cross-sectional design and reliance on self-reported sleep data.